Interleukin-12 primes CD4(+) T cells for interferon-γ production and protective immunity during Mycobacterium avium infection - Silva, Regina A (Blackwell Science Inc, 2001)
Interleukin-12 (IL-12) is a crucial cytokine for the generation of a protective immune response against Mycobacterium avium infection. In contrast to infected control mice, IL-12-deficient mice were unable to control bacterial proliferation and their spleen T cells were almost unresponsive in vitro to specific antigens of M. avium. Susceptibility of mice deficient in IL-12 was similar to that of interferon-γ (IFN-γ)-deficient mice. These data indicate a crucial role of IL-12 in the development of a T-cell population able to produce IFN-γ and to mediate protection against M. avium infection. Treatment of M. avium-infected mice with IL-12 induced CD4(+) T cells with enhanced capacity to produce IFN-γ as well as to confer increased protection against M. avium.